X‐band, mechanically‐beam‐steerable lens antenna exploiting the Risley prism concept. Issue 14 (5th October 2020) - Zhang, Zongtang; Luyen, Hung; Booske, John H.; Behdad, Nader
Abstract : This study presents a beam‐steerable antenna system that uses two mechanically‐rotatable, phase‐shifting surfaces (PSSs) functioning like a pair of Risley prisms for beam scanning operation at X‐band. One of the PSSs also acts as a lens, performing beam collimation in addition to providing a phase shift gradient. Unit cells constituting the two PSSs were co‐designed to determine the distance between the two surfaces that results in high transmission coefficients and small phase errors under different beam‐scanning conditions. Both simulation and measurement results have verified that the distance of 2 mm provides the best performance regarding to peak gain. Prototypes of the PSSs having circular apertures with diameters of 11.5 λ 0 at 10 GHz were fabricated and illuminated by a feed antenna to characterise the beam scanning performance. The measurement results of the proposed antenna system demonstrate the capability to steer the main beam within a ± 60 ° scanning range with a maximum gain variation of less than 3.6 dB by rotating the two PSSs with respect to each other. The fabricated prototype provides side lobe levels less than − 13.1 dB, polarisation purity higher than 20 dB, and small beam pointing errors of no more than 1 ° in all examined beam scan scenarios.